(untitled) (Canadian Eye Care Today, 2024)
An occlusion of the central retinal artery (CRA) or one of its branches can lead to severe acute vision loss. Patients rarely recover functional visual acuity (VA) in the affected eye, however good visual recovery can occur in transient retinal artery occlusion (RAO). Several treatment strategies have been described in the acute setting of a retinal artery occlusion (RAO). However, to date, no evidence- based treatments exist for this condition. Recently, several clinical studies have emphasized the higher risk of stroke and cardiovascular events (CVE) in patients with RAOs. As a result, urgent assessment of neurovascular risk factors in the context of an acute RAO is widely recommended.